International Venture Capital Terms: A Handbook - Weitnauer, Wolfgang (Verlag C.H.BECK Recht - Wirtschaft - Steuern, 2022)
The book compares the venture capital conditions in some of the leading industrial nations worldwide. It is divided into two parts. The first part deals with the general legal and tax framework of VC investments on the target as well as the fund level. The second part starts with a standard form of term sheet for international use. Based on this term sheet, the authors look at the major standard terms of a VC investment and their usual application in their own jurisdiction, favouring either investors or founders. An overview at the end of the book, comparing the different jurisdictions directly, helps the reader to quickly and immediately see and compare different terms and conditions. This handbook offers guidance for the use of terms for VC investments and market standards in comparison and highlights the particularities of VC investments in 15 major VC markets worldwide. It will be useful for all founders, investors and advisers.